Potensi Desa Kuwiran Sebagai Kawasan Agrowisata Padi Berkelanjutan - Siswadi & Efrain Patola (Innofarm:Jurnal Inovasi Pertanian, 2010)
ABSTRACTThe purpose of this research was to known : (1) to known potency a tour owned by CountrysideKuwiran As going concern Paddy Agrowisata Area., (2) to known response each perpetrator a tourto Countryside Kuwiran As going concern Paddy Agrowisata Area, (3) to known role from eachperpetrator wisata in realizing going concern operasionalisasi Paddy Agrowisata Area. Datacollecting of primary used technique of circumstantial interview (in depth interview) and have thecharacter of opened (open interview), while data collecting of secondary by citing tables or datawhich available from source of data.The results of this research show: : (1) countryside of Kuwiran very potential to becamePaddy Agrowisata Area have Continuation, good seen from attraction potency / object of tour,aksesibilitas, amenitas, and also hospitality, (2) local government response (On duty Tourism) tooperasionalisasi of Paddy Agrowisata Area, positive enough because although not yet there isgoals but have there is planning for the mentioned. While response of local society very positive,even expect immediately can be realized, (3) role of local government in " operasionalisasi of PaddyAgrowisata Area", for example : (a) coherent and consistency about the method of making use offarm for development of tour area, and displace farm function, (b) ready the tourism infrastructure,(c) security and freshment make a tour, (d) reinforcement of institute of tourism by facility andextend network of group and tourism organization, (e) adjacent in a promotion of tour , namelyextension and intensification of network of promotion activity in domestic and abroad, (4) thecollege have role as think tank, in charge of for executing of education socialize, related to aspect ofpower mind and culture paddy, entrepreneur, and also the training / guide courses, and others, (5)socialize Kuwiran of sharing of key in providing most attraction at one blow determine quality of tourproduct.Keyword : agrowisata of paddy, sustainable tourism